Study of Forming Factors Electronic Word of Mouth (EWOM) and Its Influence On Purchasing Fruit Products at Kojama Shop - Siti Suciani Fitriah; Budi Dharmawan; Ulfah Nurdiani (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2021)
Kojama Shop is an online platform that markets avocado butter products. To win the competition, Kojama Shop must improve Electronic Word of Mouth (eWOM) by knowing the factors that form eWOM and their effect on purchases. This study aims to determine the factors that form eWOM on the purchase of fruit products at the Kojama Shop and the influence of the factors formed from eWOM on the purchase of fruit products at the Kojama Shop. The selection of research places is intentional. The target of research is the follower of the Kojama Shop Instagram account that has already bought and consumed butter avocado fruit products at least 2 times, aged at least 18 years, and actively using social media Instagram. Data retrieval using survey methods through online questionnaires using Google forms. Sampling using the Unknown Population formula, the study took 151 respondents. Data analysis uses descriptive and multiple linear regression. The results showed that there are 5 factors of eWOM: Concern for Others, Expressing Positive Feelings, Economic Incentives, Helping the Company, and Platform Assistance. These five factors have a significant influence together and an individual towards the purchase.